The tell-tale hearts: Donor-derived invasive fungal infections among orthotopic heart transplant recipients - Jay Krishnan; Manuela Carugati; Rachel A. Miller; Cameron R. Wolfe; John R. Perfect; Julia A. Messina (Medical Mycology Case Reports)
Donor-derived invasive fungal infections among solid organ transplant recipients are rare but sometimes devastating events associated with notable morbidity and mortality. Here we describe two donor-derived fungal infections – one Candida parapsilosis complex infection and one Aspergillus fumigatus infection – that occurred among heart transplant recipients at a quaternary care center. Both recipients survived their infections, though with substantial morbidity despite aggressive surgical intervention and antifungal therapy.